Company analysis : Xiaomi Corporation / Sharif Mohamad Syazwan Sharif Ismail - Sharif Ismail, Sharif Mohamad Syazwan (2022)
This case study is about Xiaomi Corporation which is an internet company that focuses on smartphones and smart hardware that are all linked via an Internet of Things (IoT) network. Because of the company's popularity and brand name, its products are well-known around the world. We will learn to analyze, apply information, rationale, and draw conclusions from this study to gain a better understanding of this company. The first section of this case study focused on gathering company details such as the company's history, problem statement, and study intent. Any issues in the business can be found as a result of the investigation. These issues were investigated, and some ideas and improvements were suggested in order to produce a higher-quality product that is well-known among customers worldwide. The second section of the case study focuses on its history, organizational structure, goods and services, technology, industry, marketing, and operational strategy. In the third section, we use SWOT technique, which is an abbreviation for the company's strengths, weaknesses, opportunities, and threats, to analyze the company's products or services and gain a better understanding on how the company operates. The fourth section is to come out with the conclusions and discussion for this case study report about Xiaomi Corporation and the final section is for the recommendations and improvement.